The effectiveness of passive land value capture mechanisms in funding infrastructure. Issue 3 (12th November 2020) - Lee, Chyi Lin; Locke, Martin
Abstract : Purpose: This study examines the effectiveness of passive value capture mechanisms as an effective form of mechanisms in funding infrastructure from an Australian perspective. The lukewarm response of active value capture mechanisms such as betterment levies in Australia is also discussed. Design/methodology/approach: A case study of the Sydney Metro City and Southwest (SMCSW) project in Sydney is used to illustrate passive value capture mechanisms. Findings: Unlike many developed countries, passive value capture mechanisms have been adopted in Australia. This approach is an effective form of value capture mechanisms to capture the value uplift to offset the total development cost of the SMCSW project. However, this approach is highly sensitive to property transaction activities that could be affected by the general economic conditions and unprecedented events such as the COVID-19 pandemic. Further, there is a widespread discussion of the efficiency of land tax in New South Wales (NSW) in capturing all properties subject to the value uplift. Consequently, a shift towards a broad-based land tax is recommended in which it would provide a more efficient way of infrastructure funding. Practical implications: Policymakers should consider a broad-based land tax for residential and commercial properties in order to improve the efficiency of passive value capture mechanisms. This also highlights property valuers should play a greater role in the development of broad-based land tax system. Originality/value: Previous studies have extensively demonstrated property value impacts of transit investments; very little research assesses the growth of value capture funding mechanisms, particularly passive value capture mechanisms. Specifically, this paper is the first paper to assess the effectiveness of passive value capture mechanisms.